Design Studio Teaching: Creative Method in Era of 2021. - Dr. Allah dad (Journal of Peace, Development and Communication, 2022)
The education setup is considered as one of the major sectors badly affected by the COVID 19 virus around the globe. In every part of the world, all educational institutions were forced to shut down and closed during the first wave of COVID 19 virus between March 2020 to December 2020. After this, it has been realized that we all must learn and live with this virus. The educational institutions started the courses 1st on online medium and then later adopted hybrid teaching methods. Here in Pakistan the same way was adopted till up to the fourth wave of Virus from November 2020 to August 2021. But the online teaching-learning method was proved successful in theoretical subjects and therefore facing lots of issues in Studio/Lab work subjects that’s why universities were reluctant to start studio courses. The practice makes a person perfect, on this notion Design Universities decided to take a challenge and converted their studio courses onto a digital medium. In this paper, the author conducted fieldwork from different Leading Design Universities as the unit of analysis and gather information that how they converted their design studio subjects into an online system without compromising Quality of work and also without attending Labs at campuses of Different subjects such as Weaving, Knitting, Embroidery, sewing, etc. In this paper, the author presented best procedures and methods of converting Embroidery Studio Subjects into digitally and obtained 100% outcomes of Learning.